Transcatheter arterial chemoembolization is safe and effective for patients with late-stage or recurrent oral carcinoma - Bi, Yonghua; Du, Tianfeng; Pan, Wenting; Tang, Fan; Wang, Yang; Jiao, Dechao; Han, Xinwei; Ren, Jianzhuang (Frontiers in Oncology, 2022)
Objective: We aimed to report the long-term outcomes of transcatheter chemoembolization (TACE) for patients with late-stage or recurrent oral carcinoma. Methods: This retrospective study enrolled 18 patients of late-stage or recurrent oral carcinoma between December, 2015 and April, 2021. The tumor-feeding artery was catheterized, and cisplatin/oxaliplatin and 5-Fu/raltitrexed were infused with embolization using polyvinyl alcohol or gelatin sponge. Computed tomography was performed at about 1, 3, 6 months after procedure, and every about 6 months thereafter. During procedure and follow-up, procedure outcomes, complications, treatment efficacy and overall survival were analyzed. Results: A total of 31 sessions of TACE were performed, with a technical success rate of 100%.For 12 patients combined with oral hemorrhage,2 patients showed rebleeding 35 and 37 days later, with a clinical efficiency of hemostasis of 88.9%. Mild complications were observed in 11 patients (61.1%). Severe complications or procedure-related death were not observed during or after procedure. The objective response rate and disease control rate were 20.0% and 86.7%, 38.5% and 61.5%, 25.0% and 50.0% at 1, 3, 6 months later, respectively. Seventeen patients (94.4%) were followed up, with a median duration of 37.8 months (IQR 22.3, 56.8). Nine patients died of tumor progression, one died of massive rebleeding, and one died of severe lung infection. The median overall survival was 23.8 months. Conclusion: TACE is a safe and effective procedure with minimal invasiveness for the treatment of late-stage or recurrent oral carcinoma. TACE can be recommended as a palliative treatment, especially for patients with oral hemorrhage.